ICT dan Kinerja Organisasi : Peran Mediasi Inovasi - Sari, Nindira Sekar (E-Jurnal Akuntansi, 2019)
The purpose of this study was to find out how Information and Comunications Technology is influenced by innovations that become intervenig variable to organizational performance. Data from this study were obtained 70 questionnaires were distributed to employees of the Enterprise Resource Planning system users who work in PT. Housing Development, Tbk, which is one of the companies ERP users in Indonesia. Knowledge and skills variables affect the performance of the organization, while the source of information and infrastructure has no effect on organizational performance. The effect of innovation in mediating knowledge and skills and the source of information on company performance is partial mediation because the VAF values ??are in the range> 30 - <70. In addition, the innovation in mediating infrastructure for organizational performance is full mediation because the VAF values ??are in the range> 70. Limitations of this research is to only use one company as research samples, making it less able to generalize the findings. Keywords : ICT, Organizational Performance, Innovation.